Elucidation of the Problem of the Future Teachers Training to Parents Pedagogical Enlightenment in Modern Scientific Sources - Tetyana Dovzhenko (Pedagogical Discourse, 2013)
In this article the author presents the results of the analysis of the grade of the elucidation of the problems of the teachers training in Russian and Ukrainian scholars’ publications. It is stated that in modern scientific sources such aspects of the researching problem are revealed: the sources of pedagogical education in the history of Ukrainian pedagogical thought; the specific work of different types of pedagogical educational establishments of different accreditation levels in the system of continuous professional education; system analysis of the content, structure and tendencies of university pedagogical educational development (national and international contexts); multilevel training of pedagogical staff and philosophical grounding of the conceptions of professional pedagogical education renovation.